Trichomes and Stomata Diversity in Soybean (Glycine max L. Merill) Lines. Issue 1 (May 2019) - Amaliah, N; Zubaidah, S; Kuswantoro, H
Abstract: Modified epidermal tissues on the leaf surfaces, such as trichomes and stomata, are very useful for plants because it helps prevent pest attacks and support photosynthesis. The characteristics of a plant can be determined based on an observation conducted on trichomes and stomata to improve the genetic potentials of the plant. This research aimed to discern the diversity of trichomes and stomata in 10 soybean lines and determine the correlation between the characters. This experimental study employed a randomized complete block design with three replications. The results showed that there were significant differences in all leaf anatomical characters including the number of trichomes and stomata, as well as the length and the width of the trichomes and stomata. Some observed characters were also correlated. Positive correlations were found between the number of stomata and the width of the trichomes, the width of the lower stomata and the length of the trichomes, and the width of the upper stomata and the width of the trichomes. On the other hand, a negative correlation was observed between the length of the stomata and the number of trichomes.